Mood and anxiety disorders within the Research Domain Criteria framework of Positive and Negative Valence Systems: a scoping review - Böttger, Sarah Jane; Förstner, Bernd R.; Szalek, Laura; Koller-Schlaud, Kristin; Rapp, Michael A.; Tschorn, Mira (Frontiers in Human Neuroscience, 2023)
Introduction While a growing body of research is adopting Research Domain Criteria (RDoC)-related methods and constructs, there is still a lack of comprehensive reviews on the state of published research on Positive Valence Systems (PVS) and Negative Valence Systems (NVS) in mood and anxiety disorders consistent with the RDoC framework. Methods Five electronic databases were searched to identify peer-reviewed publications covering research of “positive valence” and “negative valence” as well as “valence”, “affect”, and “emotion” for individuals with symptoms of mood and anxiety disorders. Data was extracted with a focus on disorder, domain, (sub-)constructs, units of analysis, key results, and study design. Findings are presented along four sections, distinguishing between primary articles and reviews each for PVS, NVS, and cross-domain PVS and NVS. Results A total of 231 abstracts were identified, and 43 met the inclusion criteria for this scoping review. Seventeen publications addressed research on PVS, 17 on NVS, and nine covered cross-domain research on PVS and NVS. Psychological constructs were typically examined across different units of analysis, with the majority of publications incorporating two or more measures. Molecular, genetic, and physiological aspects were mainly investigated via review articles, primary articles focused on self-report, behavioral, and, to a lesser extent, physiological measures. Conclusions This present scoping review shows that mood and anxiety disorders were actively studied using a range of genetic, molecular, neuronal, physiological, behavioral, and self-reported measures within the RDoC PVS and NVS. Results highlight the essential role of specific cortical frontal brain structures and of subcortical limbic structures in impaired emotional processing in mood and anxiety disorders. Findings also indicate overall limited research on NVS in bipolar disorders and PVS in anxiety disorders, a majority of self-report studies, and predominantly observational studies. Future research is needed to develop more RDoC-consistent advancements and intervention studies targeting neuroscience-driven PVS and NVS constructs.